SAMGITA PANCASONA KARYA SARDONO DALAM FENOMENA KONFLIK TRADISI – MODERN - Budi Santosa (SURYA SENI, 2008)
Artistic journey of Surakarta dance, in its growth coloured by many various dynamic event, for example incidence of conﬂ ict. For example, event which enough the legend and have various dimension mean that is hard deduction of tradition society to show of dance Samgita Pancasona masterpiece of SardonoW. Kusumo in RRI Surakarta in the year 1970s. That ocurance generate hard collision among/between of tradition and modern movement. Afterwards, then is opened by the new ﬁ rmanent  which open various possibility door to develop various concept and idea creation of dance, including use of modern dance motion material and technique. The interesting problems is Yayasan Seni Budaya Indonesia (YASBI) attitude which openly perform a deduction to movement renewal of Pusat Kebudayaan Jawa Tengah (PKJT) supporting modern  movement. From that case there are two important matter which is properly noted is, First, is YASBI attitudeassuming taboo show of contemporary dance of Sardono W. Kusumo and assumed to endanger. Second, is historical side, specially related to effort to know renewal growth dance in Surakarta. On the basis of that importance, hence thisresearch was designed to know how occurrence of tadition – modern conﬂ ict in artistic society of show of Surakarta which is in the form of deduction to contemporary dance Samgita Pancasona masterpiece of Sardono in the year 1970in RRI Surakarta. So that is reaching critical reﬂ ectionof reasearch will be come near with Theory of Conﬂ ictof Ralp Dahrendorf which ever look into society always stay in change process, marked by continuous oposition amongits elements.Result of research to show of that all modern  dance exponent in Surakarta, have surprised tradition society. On the other hand YASBI following movement of tfradition feel annoyed. In turn happened  tradition-modern conﬂ ict causing  at throwing of buthuk egg tos how of contemporary dance Samgita Pancasona. That occurrence as symbol that tradition society refuse attendance of modern dance inﬂ uence which destroy of the social order of the dance Surakarta. Its top is enragement of YABI head, Moedhakir Wiroguno then to attack PKJT,modern movement center by riding Jeep car climb Pendopo of Sasanamulya tha is as bravery symbol to defeat foreign inﬂ uence which destroy tradition values.That occurrence in the end open new awareness of tradition dance can be made by items for the basic  of contemporary dance. That event, is short lived even if, undeniably have very long inﬂ uence to life Surakarta dance later on day. The inﬂuence for example, opening various possibility door, both for concerning idea, artistic creation, and also study to dance art, including also reinforcemnet of tradition, in consequence in Surakarta growth dance proportional contemporary dance and tradition. Thereby result of the reasearch in harmony with assumption  which have been raised.Keywords: tradition and modernity conﬂ ict